Balto-Slavic *nai̯g-, a neglected isogloss with external relatives - Blažek, Václav (Baltistica, 2025)
The relationship of the Latvian verb naigât, -ãju and the adj. naîgs with the Slavic noun *ně̋ga and verb *něgati was identified already by Bezzenberger and Fick in 1881. Later attempts to add new comparanda have not been convincing. The present contribution discusses possible cognates in Tocharian and Celtic, implying the Indo-European protoform *nei̯gu̯-.
Keywords: latvių kalba; slavų kalbos; tocharų kalbos; keltų kalbos; teigiama emocija